Investigating Gender Differences in Senior High School Students’ Motivation to Learn English Online During The COVID-19 Pandemic - Wahyu Setyo Prihandono; Bibit Suhatmady; Weningtyas Parama Iswari (Educational Studies: Conference Series, 2021)
A lot of research has been conducted to examine the effect of gender differences on language learning motivation in various learning environment, yet the outcomes remain contradictory. This study investigates gender differences in 568 Indonesian senior high school students’ motivation to learn English online during the COVID-19 pandemic. In this quantitative enquiry, the data were collected using a motivational questionnaire containing a number of items indicating motivational components. One-way MANOVA was performed to examine not only the students’ overall motivation, but also the effect of gender differences on three motivational variables, namely instrumental orientation, self-efficacy beliefs, and self-regulation. The findings revealed that the students’ overall motivation differs by gender. Furthermore, it was indicated that, in general, female students possessed higher levels of motivation than male students in learning English online. The results support the growing stereotype claiming that female learners tend to outperform their male peers in language learning. The analyses on the motivational variables indicated that female students had higher level of instrumental orientation and they were more self-regulated compared to male students. In terms of their self-efficacy beliefs, no significant differences detected between male and female students in learning English online during the COVID-19 pandemic.